Cytotoxic substances from two species of Japanese sea hares: chemistry and bioactivity - Yamada, Kiyoyuki (The Japan Academy, 2010)
From the sea hares belonging to two genera, Aplysia and Dolabella, a variety of new cytotoxic substances were isolated as minute constituents: their chemical structures were determined and their cytotoxicity was evaluated. Regarding the highly cytotoxic substances, further chemical and biological studies were performed that included their asymmetric chemical synthesis and elucidation of biological characteristics such as antitumor activity.